Is the conservative non-surgical management of medication-related osteonecrosis of the jaw an appropriate treatment option for early stages?: A long-term single-center cohort study - Ristow, Oliver; Rückschloß, Thomas; Müller, Michael; Berger, Moritz; Kargus, Steffen; Engel, Michael; Hoffmann, Jürgen; Freudlsperger, Christian (Journal of cranio-maxillofacial surgery, 2019)
Purpose - No consensus has been reached regarding the best treatment option for early-stage lesions in medication-related osteonecrosis of the jaw (MRONJ). The purpose of the present study was to evaluate the long-time outcomes of conservative non-surgical management in stage I patients with underlying malignant disease. - Materials and methods - We designed and implemented a retrospective cohort study and enrolled, between 2008 and 2018, a sample of patients with the indication for non-surgical conservative treatment stage I lesions. The primary outcome variable was treatment success defined as mucosal integrity without signs of infection. Secondary outcomes were: (i) worsening stage, (ii) necessity for surgical intervention over time, and (iii) discontinuation of antiresorptive therapy. - Results - The sample included 75 patients with 92 lesions. Eight lesions showed full mucosal coverage, whereas 84 continued with exposed jaw bone (91.3%). Of the treatment-resistent 84 lesions, 67 presented a worsening stage shift over time. Indication for surgical intervention was set in 57 lesions. Of all lesions, 28 developed highly advanced necrotic bone destruction. Antiresorptive medication was paused in all evaluated patients after the first diagnosis of MRONJ. - Conclusion - Conservative non-surgical therapy in MRONJ stage I leads to a healing in rare cases. Conservative management might be a good option to preserve symptoms in patients either unwilling to undergo surgery or in those whose reduced general condition does not allow surgery. Early and consequent surgical advances should be performed throughout all stages of the disease to prevent the possibility of silent disease progression with the risk of large-scale bone loss.
Available online 29 December 2018
Gesehen am 27.08.2019